Facilitators and Solutions for Practicing Optimal Guided Asthma Self-Management: The Physician Perspective - Alexandrine J Lamontagne; Sandra Peláez; Roland Grad; Lucie Blais; Kim L Lavoie; Simon L Bacon; Hélène Guay; Annie Gauthier; Martha L McKinney; Pierre Ernst; Johanne Collin; Francine M Ducharme (Canadian Respiratory Journal)
OBJECTIVE: To identify key solutions that facilitate the prescription of long-term asthma controller and provision of written self-management plans by physicians.